Olfactory Ensheathing Cell Tumor Arising from the Olfactory Mucosa - Eriko Ogino-Nishimura; Takayuki Nakagawa; Yoshiki Mikami; Juichi Ito (Case Reports in Medicine)
We report a rare case of olfactory ensheathing cell tumor. A female presented a large soft mass extending medially to the olfactory cleft and laterally to the middle meatus in the left nasal cavity. Imaging studies confirmed a cystic mass extending superiorly into the frontal lobe, indicating that the tumor arouse from the olfactory mucosa. A subtotal resection was achieved through an endoscopic endonasal approach without operative complications. Immunohistochemically constituent cells were diffusely positive for S-100 protein, but olfactory ensheathing cell tumor was diagnosed by negative staining for Leu7 (CD57). This case indicates that olfactory ensheathing cell tumor should be included in differential diagnoses for the olfactory cleft tumors.